MEMBANGUN WEBSITE NATIONAL PARALYMPIC COMMITTEE ( NPC ) INDONESIA DI SURAKARTA SEBAGAI SARANA PUBLIKASI MASYARAKAT - Sipahutar, Revy (Gaung Informatika, 2014)
The website has now become a power in modern times. Website becomes a tool of media  information  that  are  easy  to  execute  and  understood  by  the  community. NPC is less published information among the general public from background of the  problem  is  the  website  is  designed  to  facilitate  local  and  inter -local communities see and follow NPC news quickly and easily. One of the problems media information becomes weakness NPC in the field  of website that can not be handled  by  the  NPC,  the  website  can  impress  all  NPC  employees  working conditions. This final project aims to build a website that is used to process and store  data  information,  about  data  news  and  activities  NPC.  This  website  is expected  to  provide  convenience  of  visitors  in  search  of  information  about  and also NPC. This website built using HTML, PHP and uses a MySQL database, by using Macromedia Dreamweaver. Testing a website using WebQual method with 30  respondents  consisting  of  four  dimensions,  (usability,  information  quality, information quality and overall), website get value of 79,9% acceptable value.